2017
DOI: 10.1186/s13063-017-2066-5
|View full text |Cite
|
Sign up to set email alerts
|

Tight intra-operative blood pressure control versus standard care for patients undergoing hip fracture repair – Hip Fracture Intervention Study for Prevention of Hypotension (HIP-HOP) trial: study protocol for a randomised controlled trial

Abstract: BackgroundHypotension during anaesthesia for hip fracture surgery is common. Recent data suggest that there is an association between the lowest intra-operative blood pressure and mortality, even when adjusted for co-morbidities. This is consistent with data derived from the wider surgical population, where magnitude and duration of hypotension are associated with mortality and peri-operative complications. However, there are no trial to data to support more aggressive blood pressure control.Methods/designWe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…This may be an effect due to combined spinal and epidural anaesthesia being chosen for more complex procedures; however, this is merely speculation. Tight haemodynamic control maintaining blood pressure and heart rate within minimal deviation from preoperative values have been suggested to have a major impact, and studies assessing its effect are being conducted 13 . Optimising haemodynamics by ultrasound monitoring may also facilitate the perioperative course 14 .…”
Section: Discussionmentioning
confidence: 99%
“…This may be an effect due to combined spinal and epidural anaesthesia being chosen for more complex procedures; however, this is merely speculation. Tight haemodynamic control maintaining blood pressure and heart rate within minimal deviation from preoperative values have been suggested to have a major impact, and studies assessing its effect are being conducted 13 . Optimising haemodynamics by ultrasound monitoring may also facilitate the perioperative course 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Feature selection is a key technology used in imaging evaluation. It maintains the recognition accuracy after removing irrelevant features on the basis of maintaining the original target features, and it can be applied to imaging evaluation after fracture [ 7 , 8 ]. According to the types of network data, feature selection algorithms can be divided into semisupervised feature selection (SSFS), supervised feature selection (SFS), and unsupervised feature selection (UFS).…”
Section: Introductionmentioning
confidence: 99%
“…A recent prospective randomised controlled trial in younger, but higher risk, patients found that patients randomised to receive maintenance of intraoperative arterial blood pressure close to baseline had significantly reduced postoperative major morbidity compared with those randomised to standard intraoperative arterial blood pressure management [13]. Another ongoing multi-centre pilot study aims to assess outcomes in older hip fracture patients (aged more than 70 years) by randomising then between tight intraoperative blood pressure control and standard care [34]. This cohort of frail patients who had sustained hip fractures were at a high risk of organ failure even before surgery, as illustrated by their high Charlson Comorbidity Index (mean 5.7, estimated 10-year survival 2-21%).…”
Section: Discussionmentioning
confidence: 99%